Crop Residue Orientation Influences Soil Water and Wheat Growth Under Rainfed Mediterranean Conditions - George Swella; Phil Ward; Kadambot H. M. Siddique; Ken C. Flower (Agronomy, 2025)
Under rainfed Mediterranean-style conditions, crop growth and yield are largely determined by the availability of water. We investigated the role of residue orientation (standing or horizontal) and quantity on temperature, soil water, and wheat growth in two experiments with annual (winter) cropping. In the first trial at Shenton Park, tall (0.3 m) standing residues combined with thick (4 t ha−1) horizontal residues increased the soil water at sowing by more than 100 mm compared with the bare soil control, increasing the wheat yield by about 2 t ha−1. The average soil water storage was linearly related to the total residue quantity (r2 = 0.86). Both standing and horizontal residues reduced the daily soil temperature fluctuations, but increased the air temperature fluctuations. Tall-cut residues had higher maximum and lower minimum air temperatures 0.05 m above the ground than short-cut residues with more horizontal material. Under field conditions, more soil water was stored in the growing season with the residues cut relatively tall with less on the ground compared with an equivalent residue amount consisting of shorter residues with more on the ground, although the differences were not great. Tall stubble was also associated with greater green leaf area and PAR interception. At the Cunderdin trial, the residue was greater between the harvester wheel tracks than at the outer edge of the cutting front. Under the very dry seasonal conditions experienced during the trial, greater residue resulted in increased soil water storage, particularly in the top 0.5 m of soil (up to 29 mm), greater green leaf area index, and higher crop yields (up to 300 kg ha−1) behind the harvester, associated with greater spike m−2, greater spikelets spike−1, and lower root:shoot ratio. These results demonstrate the importance of considering residue orientation to maximise crop water use efficiency and yield.